A Practical Clinical Protocol for Monitoring Patients with Severe Uncontrolled Chronic Rhinosinusitis with Nasal Polyposis Treated with Biologics. (January 2022) - Millarelli, Stefano; Loperfido, Antonella; Mammarella, Fulvio; Giorgione, Cristina; Celebrini, Alessandra; Del Ninno, Massimiliano; Bellocchi, Gianluca
Objectives: Chronic rhinosinusitis with nasal polyposis (CRSwNP) is a pathological condition which leads to high healthcare-related costs and low quality of life for patients. The introduction of new biological therapies (monoclonal antibodies, MAbs) in CRSwNP patients has allowed new therapeutic options for non-responders to conventional therapies and Dupilumab represents the first approved biological agent. The aim of this paper is to provide a practical clinical multidisciplinary protocol which might help clinicians involved in this field to monitor the clinical outcomes. Methods: Our centre of Rhinology and Rhino-Allergology has developed a dedicated collection form to observe the outcomes of patients treated with Dupilumab. Our research started from the indications given in EPOS 2020 as main reference. We then implemented these references in an electronic database trying to apply Evidence Based Medicine (EBM) in current clinical practice. Results: The result consists of three parts: an anamnestic collection data, a clinician reported outcome and two patient reported outcomes (PROMs) questionnaire, the visual analogue scale (VAS) and the Sino-Nasal Outcome Test-22 (SNOT-22). The tables we propose should provide an adequate correlation with the patients' adherence to therapy and their treatment outcomes. Such periodical evaluation (after a month, after 3 months, after 6 months and at one year) should quickly allow to monitor if the patient is correctly assuming the therapy and the eventual objective improvements. Conclusions: We propose a practical monitoring protocol formulated to analyse both objective and subjective aspects of patients with severe uncontrolled CRSwNP treated with MAbs, thus helping to define in future a better comparison between the clinical results of different institutes.